Diurnal Variations in Anterior Segment Parameters in Different Grades of Patients With Keratoconus - Xiahou, Jinxuan; Ning, Rui; Xu, Shuoyu; Li, Kexin; Gustafsson, Ingemar; Wang, Yiran; Yang, Xinning; Zhou, Xingtao; Huang, Jinhai (Translational Vision Science and Technology, 2025)
Purpose: This study aims to evaluate the diurnal variations in anterior segment parameters among patients with keratoconus (KC) and to compare these variations across different severity levels of the disease. Methods: A total of 82 patients with KC were included in the study. Corneal parameters were measured at 08:30, 11:30, 14:30, 17:30, and 20:30 using the Pentacam HR (Oculus, Wetzlar, Germany). The eyes were graded as mild, moderate, or severe KC according to the Topographical Keratoconus Classification system. The Kolmogorov–Smirnov test was applied to assess the normality of the data distribution. Diurnal variations in these parameters were analyzed using repeated-measures analysis of variance. Results: Significant diurnal variations were found in central corneal thickness (CCT) and thinnest corneal thickness (TCT) in patients with KC. The mean amplitude of change between 08:30 and 11:30 was 5.73 μm for CCT and 5.83 μm for TCT. These variations were significant in mild to moderate KC but not in severe KC. In addition, corneal volume showed significant diurnal variations in all KC, while keratometry and anterior chamber depth did not. Conclusions: The study highlights that significant diurnal variation in corneal and anterior chamber parameters, specifically CCT and TCT, is prominent in patients with KC, especially those with mild and moderate disease severity. Translational Relevance: The results of the diurnal variation patterns of anterior segment parameters in patients with KC contribute to the evaluation of surgical safety and the assessment of follow-up progression. These research findings provide a basis for clinicians to better manage the condition of patients with KC.
Keywords: anterior segment parameter; diurnal variation; keratoconus